The "sanctity" of marriage – an archaeology of a socio-religious construct: Mythological origins, forms and models - Dreyer, Yolanda (HTS teologiese studies, 2008)
The aim of the article is to argue that the sexual difference between female and male should be regarded as soteriologically indifferent. Though a biological reality of being human, sexuality is profoundly influenced by social constructs and the institution of marriage itself is a social construct. In this article the biological and social aspects are taken into account in a theological approach which on the one hand is interested in the relationship between God and human beings, and on the other in the way in which the Bible elucidates sexuality and marriage. The article indicates that the idea of sexual intercourse between a man and a woman as being equal to Godgiven “holy matrimony” has mythological origins. It focuses on these origins and on the multifarious forms of marital arrangements and models.